2013
DOI: 10.1007/s13202-013-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

Oil mobilisation by subcritical water processing

Abstract: As water approaches the critical point, the dielectric constant lowers enabling solution of heavy oil components. Simultaneously, enhanced water dissociation enhances cracking to lighter fractions. We evaluated this effect for three heavy oils concentrating on the effect of processing on feed viscosity. Reductions of up to 90 % were observed and these could be achieved in a few hours. Although more applicable to surface processing of oil sands in the short term, ultimately this technique could also be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…10 -14 . The resulting higher H?/OHconcentration enhances cracking potential (Ryan et al 1997;Patrick et al 2001;Akiya and Savage 2002;Golombok and Ineke 2013). By contrast, supercritical water relies solely on its increased thermal cracking potential (Ogunsola and Berkowitz 1995;Kamimura et al 1998;Deng et al 2011;Park and Son 2011;Deng et al 2012;Golombok and Ineke 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -14 . The resulting higher H?/OHconcentration enhances cracking potential (Ryan et al 1997;Patrick et al 2001;Akiya and Savage 2002;Golombok and Ineke 2013). By contrast, supercritical water relies solely on its increased thermal cracking potential (Ogunsola and Berkowitz 1995;Kamimura et al 1998;Deng et al 2011;Park and Son 2011;Deng et al 2012;Golombok and Ineke 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SCW has several potential applications, including extracting oil from oil shale lumps (Deng et al 2011), sulphur removal (Kamimura et al 1998;Park and Son 2011), tar sands (Park and Son 2011) and the cracking of heavy hydrocarbons into lighter fractions (Duan et al 2013;Golombok and Ineke 2013), thereby reducing the viscosity. The use of catalysts to enhance near critical effects has recently been extensively reviewed (Tumanyan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus subcritical water can convert AS and coke into valuable MA. Golombak and Ineke [27] in 2013 disclosed that the hot water can pyrolytically crack the long molecular weight structures. Literature revealed that the hydrothermal reaction mechanism depends on water density: the reaction is controlled by the ionic reaction mechanism at high water density and low temperature; whereas the free radical reaction mechanism is prevalent at low water density and high temperature [28]- [30].…”
Section: Resultsmentioning
confidence: 99%
“…The respective subscripts (l) and (aq) refer to the hydrocarbon components present as pure water-insoluble liquid as found at ambient condition and dissolved in water under subcritical conditions. The ions, [H + ] and [OH -], are the respective concentrations of hydrogen and hydroxide ions arising from dissociation of water as [27]:…”
Section: Resultsmentioning
confidence: 99%
“…Golombak and Ineke [25] in 2013 disclosed that the hot water can pyrolytically crack the long molecular weight hydrocarbon structures. Literature review revealed that the hydrothermal reaction mechanism depends on water density: the reaction is controlled by the ionic reaction mechanism at high water density and low temperature; whereas the free radical reaction mechanism is prevalent at low water density and high temperature [26], [27].…”
Section: Resultsmentioning
confidence: 99%